2017
DOI: 10.1021/acs.jproteome.6b00975
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Lipid Profiling of High Density Lipoprotein Particles in Healthy Subjects with Low, Normal, and Elevated HDL-Cholesterol

Abstract: Recent studies suggest that the cholesterol content of HDL (high density lipoproteins) may provide limited information on their antiatherogenic properties and that the composition and particles' structure provide more information on their functionality. We used NMR-based (nuclear magnetic resonance-based) lipidomics to study the relationships of serum HDL-C (HDL-cholesterol) levels with the lipid composition of HDL particles in three groups of subjects selected on the basis of their HDL-C levels. Subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Also, the protective effect of HDL 3 may be altered in people with hyperlipidaemia. In studies based on various methods, including nuclear magnetic resonance, lipid profile differences in HDL molecules have been shown to be dependent on baseline levels of this lipoprotein fraction [34]. In people with familial hypercholesterolaemia, HDL 3 molecules contain an increased amount of sphingomyelin and saturated fatty acids, resulting in an increase in lipoprotein surface stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the protective effect of HDL 3 may be altered in people with hyperlipidaemia. In studies based on various methods, including nuclear magnetic resonance, lipid profile differences in HDL molecules have been shown to be dependent on baseline levels of this lipoprotein fraction [34]. In people with familial hypercholesterolaemia, HDL 3 molecules contain an increased amount of sphingomyelin and saturated fatty acids, resulting in an increase in lipoprotein surface stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…In total, we identified eight studies using NMR or LC-MS for lipidomic analyses, all based on a relatively small sample size (number of participants ranging from 20 to 159). Most of the studies were conducted in hospital settings using cross-sectional or case-control designs [59][60][61][62][63][64][65]. Three studies conducted lipidomics of HDL and non-HDL particles [51,52,64], while five studies specifically focused on the lipidome of HDLs [61][62][63]65,66].…”
Section: Summary Of Recent Studies On Lipidomics Of Lipoproteins and mentioning
confidence: 99%
“…Most of the studies were conducted in hospital settings using cross-sectional or case-control designs [59][60][61][62][63][64][65]. Three studies conducted lipidomics of HDL and non-HDL particles [51,52,64], while five studies specifically focused on the lipidome of HDLs [61][62][63]65,66]. Of the five studies, two studies examined varieties in HDL lipid content, comparing participants with high HDL-c to those with low HDL-c [61,66], and the other studies focused on the lipidome of lipoproteins and CHD diagnosis and progression [51,52,[62][63][64][65].…”
Section: Summary Of Recent Studies On Lipidomics Of Lipoproteins and mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, lipoprotein profiles showed significantly lower plasma concentrations of cholesterol-IDL, triacylglycerides-IDL and HDL in mothers of growth-restricted fetuses compared to controls. 1 H NMR-based lipidomic analysis of HDL lipoprotein of plasma samples, isolated from non-HDL lipoproteins by precipitation, helps in the characterization of the atheroprotective function of HDL and the identification of novel biomarkers of cardiovascular risk [18]. Jimenez et al reported an extensive NMR trial of quantitative lipoprotein in human blood serum and plasma.…”
Section: Nmr Techniques Can Provide Absolute Quantification Of Lipidsmentioning
confidence: 99%